Israel Recovers Troves of Documents Belonging to Its Most Famous Spy - Moses, Claire (The New York Times, 2025)
Israel has long sought to bring home from Syria the remains of Eli Cohen, whose spying work is credited with helping Israel win the Arab-Israeli War of 1967.
Israel
Keywords: Archives and Records; Cohen; Eli (1924-65); Damascus (Syria); Defense and Military Forces; Espionage and Intelligence Services; Israel; Mossad; Netanyahu; Benjamin; Syria